(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Introduction: Breast cancer is the second most common cancer (10.4 % of all cancer incidence, both sexes counted) and the fifth most common cause of cancer death in the world. In 2005, breast cancer caused 502,000 deaths worldwide. Clinical evaluation could function as a valuable diagnostic tool. Clinical evaluation, however, is a simple method to detect cases as it is inexpensive and non-invasive and if found to be accurate, might be of great value. Aim: To evaluate patients referred to colposcopy clinic in BSMMU for breast symptoms by clinical breast examination (CBE). Material and method: The study design was cross sectional study done in the colposcopy clinic in the department of Obstetrics and Gynaecology, under the Establishment of National centre for cervical and breast cancer screening and training at BSMMU and Cervical and breast cancer screening and training in BSMMU projects. Result: A total of 752 patients fulfilled the inclusion criteria , demographic features are demonstrated in mean age of the patients was 35.1±9.2 years, mean BMI was 22.5±2.1, about 30% subjects were postmenopausal and about 2% patients had history of breast cancer. Presenting complaint was a self-detected breast mass and found to have a mass on examination by her physician in 204 patients. 308 subjects complained of mastalgia; 34 patients complained of nipple discharge. Only 5 patients complained of axillary lymph node enlargement. Nipple abnormalities like retracted and cracked nipple was complained by 4% cases. Most patients (58%) were found to have normal findings. Palpable mass was found in 121 cases and bilateral in one case. Nipple abnormalities found in 10 cases. Tenderness and nipple discharge found in 15% and 4% cases respectively. Regarding the characteristics of the masses proved by cytology (FNAC), 109 were benign and 12 were malignant. Conclusion: CBE is an important screening procedure to identify breast pathology. Out of 752 patients breast pathology were identified in about 41% of patients and 10% breast lumps were malignant. So CBE should be done every three yearly in <40 and yearly in above 40 years women. J. Paediatr. Surg. Bangladesh 5(1): 20-24, 2014 (January)